A pilot randomized controlled study of the effects of an educational training program on skin reactions induced by chemotherapy, Epidermal Growth Factor Inhibitor (EGFRI) treatments, and immunotherapy - Papoui, Eleni; Papastavrou, Evridiki; Merkouris, Anastasios; Charalambous, Andreas (My University, 2022)
Purpose: To evaluate the effectiveness of an educational program for cancer patients who developed pruritus, rash or photosensitivity induced by chemotherapy, epidermal growth factor inhibitor (EGFRI) treatments, or immunotherapy. Method: This study is a pilot randomized controlled study. The patients in the experimental pool were assigned to attend the educational program once weekly, for 4 weeks. For the patients in the control group the usual information was provided to them, as with any cancer patient who initiates treatment. Each participant’s induction day to the program (symptoms initiation) was considered part of week 0. For the Primary endpoint repeated measurements were taken weekly regarding the grade of skin reaction. For the Secondary endpoint the 36-Item Short Form Survey questionnaire (SF-36) (since week 0) and the Dermatology Life Quality Index (DLQI) questionnaire (since week 1) were recorded. Results: The study was conducted between January 2019 and December 2020 and included 40 patients. The grades of skin reactions, showed a statistically significant improvement in the intervention group compared to the control (Walds X2 = 19,25, p = 0.004). The results from the SF-36 questionnaire, showed that patients in the intervention group presented higher functional health and wellbeing status, although the results did not indicate a significant interaction between Group and Time, for all the questionnaire parameters. The effect size difference between control and intervention groups was higher at week 3 (d = 0.44) according to the results of DLQI questionnaire. Conclusions: Further validation of the effectiveness of the educational program over longer periods of time will be required.
Keywords: Chemotherapy; EGFRI; Educational; Immunotherapy; Photosensitivity; Pruritus; Rash